Bloodline, heartline - Sarmento, Julião 1948-2021 (MER. Paper Kunsthalle, 2012)
The artist Julião Sarmento grew up with a somewhat complicated background. This book is a testimony to his "real" biological family and his "other" foster family. The first part of the book; "Bloodline", has all the photographs the artist could find of his biological family up to his birth, they show persons he often doesn't feel connected to or hardly knows. "Heartline" has all the photographs he could find of the two people in his foster family. They are close to his heart, far from his blood
Keywords: Sarmento, Julião -- 1948-2021; Identität -- Motiv; Künstlerbuch; Familie -- Motiv; Bildband